A Preliminary Study on the Use of Haptic Feedback to Assist Users with Impaired Arm Coordination During Mouse Interactions - N. G. Tsagarakis; D. G. Caldwell (Applied Bionics and Biomechanics)
Physical movement impairments caused by central nervous system dysfunction or by muscle spasms generated from other neurological damage or dysfunction can often make it difficult or impossible for affected individuals to interact with computer generated environments using the conventional mouse interfaces. This work investigates the use of a 2 dimensional haptic device as an assistive robotic aid to minimize the effects of the pathological absence of motor control on the upper limb in impaired users while using a mouse interface. The haptic system used in this research is a two degree of freedom (DOF) Pantograph planar device. To detect the intended user motion, the device is equipped with force sensing allowing the monitoring of the user applied loads. Impedance based techniques are used to develop a “clumsy” motion suppression control system. The erratic motion suppression techniques and the experimental system setup are evaluated in two dimensional tracking tasks using a human subject with failure of the gross coordination of the upper limb muscle movements resulting from a disorder called ‘Muscle Ataxia’. The results presented demonstrate the ability of the system to improve the tracking performance of the impaired user while interacting with a simple computer generated 2D space.